2009
DOI: 10.1080/01973530903058276
|View full text |Cite
|
Sign up to set email alerts
|

The Joint Impact of Achievement Goals and Performance Feedback on Information Giving

Abstract: This research examined how performance feedback moderates the effects of individuals' achievement goals on information exchange when carrying out a novel and complex task. Experiment 1 demonstrated that mastery goal individuals who received positive performance feedback gave less modified information about their task performance to their exchange partner relative to both mastery goal individuals who received negative feedback and performance goal individuals (who received either negative or positive feedback).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…This finding is in line with earlier research showing that mastery goal individuals adopt an orientation toward reciprocity when engaged in information exchange (Poortvliet et al 2007). Such an orientation also coincides with making attempts to provide an exchange partner with valuable information, even when one's own competence turns out to be low (Poortvliet et al 2009b). In accordance with such a cooperative mindset, the current study showed that mastery goal individuals are willing to give accurate information to both lowly and highly competent exchange partners.…”
Section: Studysupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in line with earlier research showing that mastery goal individuals adopt an orientation toward reciprocity when engaged in information exchange (Poortvliet et al 2007). Such an orientation also coincides with making attempts to provide an exchange partner with valuable information, even when one's own competence turns out to be low (Poortvliet et al 2009b). In accordance with such a cooperative mindset, the current study showed that mastery goal individuals are willing to give accurate information to both lowly and highly competent exchange partners.…”
Section: Studysupporting
confidence: 91%
“…In their work on leader-member exchange, Janssen and Van Yperen (2004) showed that performance goals, but not mastery goals, were negatively related to the perceived quality of the exchange relationship between supervisors and employees. Research by Poortvliet et al showed that performance goals, relative to mastery goals, lead to a reduced willingness to share valuable information with exchange partners (Poortvliet et al 2007(Poortvliet et al , 2009b. Also, relative to performance goals, mastery goals were related stronger to backing up behavior, the provision of resources and effort to help team members who are apparently failing to perform well (Porter 2005).…”
Section: Toward a Social Understanding Of Achievement Goalsmentioning
confidence: 99%
“…Although people with mastery-avoidance goals may believe that others may help them to reach their mastery goal (Poortvliet et al, 2009b), we posit that long-term striving for mastery-avoidance goals is a rather taxing form of achievement regulation. Indeed, like De Lange et al (2010) mention, "mastery-avoidance goals include a negative outcome as anchor for self-regulation."…”
Section: Social Mechanisms In Mastery Goal Pursuitmentioning
confidence: 95%
“…Earlier studies have demonstrated that mastery-approach goals give rise to interpersonal mechanisms that may support successful goal attainment such as a focus on reciprocal helping (e.g. Poortvliet, Janssen, Van Yperen, & Van de Vliert, 2009b), while these mechanisms are absent in the pursuit of performance goals. Indeed, performance goals may even give rise to rather competitive tendencies (Poortvliet, Anseel, Janssen, Van Yperen, & Van de Vliert, 2012).…”
Section: Achievement Goalsmentioning
confidence: 99%
See 1 more Smart Citation